Non-Hodgkin's lymphoma risk derived from exposure to organic solvents: a review of epidemiologic studies - Marco Antônio V. Rêgo
The rate of non-Hodgkin's lymphomas (NHL) has increased around the world during the last decades. Apart from the role of the human immunodeficiency virus (HIV) infection in the development of NHL, exposure to chemical agents like phenoxyacetic pesticides, hair dyes, metal fumes and organic solvents are suspected to be involved. The present review evaluates the results of studies that directly or indirectly searched for an association between solvent exposure and NHL. The selected studies comprised those published from 1979 to 1997, designed to investigate risk factors for NHL, whether specifically looking for solvent exposure or for general risks in which solvent exposure could be included. In 25 of the 45 reviewed studies (55.5%), fifty-four statistically significant associations between NHL and solvent exposure related occupations or industries were reported. Statistical significance was more frequently shown in studies where solvent exposure was more accurately defined. In eighteen of such studies, 13 (72.2%) defined or suggested organic solvents as possible risk factors for NHL.